Pengenalan Potensi Pariwisata Budaya Kajang sebagai Upaya Penguatan Nilai Kearifan Lokal Bagi Mahasiswa - Nasir Nasir; Sirajuddin Saleh; Nasaruddin H; Haerul Haerul; Henri Henri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Local wisdom is an important part of a nation's cultural identity, but its existence is beginning to be marginalized in the midst of modernization. The Kajang Indigenous People in Bulukumba Regency, South Sulawesi, are one of the communities that still maintain their traditional values through a customary legal system called Pasang ri Kajang. This community service activity aims to introduce the potential of Kajang cultural tourism to students as an educational effort in instilling the values of local wisdom. The partners in this activity are the Kajang indigenous people and local traditional leaders, including Ammatoa as the traditional leader. The activity is carried out with a participatory and educational method based on direct experience, which involves students in observation, discussion, and reflection on local culture. The results of the activity showed an increase in student knowledge by 31% and a significant change in attitudes towards the preservation of local culture, where more than 80% of participants showed an appreciative attitude towards the values inherited by the Kajang community. This activity also received a positive response from the local community because of its approach that respects traditional values. In addition, this activity produces several outputs, such as cultural introduction modules, activity documentation, and draft service articles. This activity shows that student involvement in the introduction of local culture can be an effective strategy in building multicultural awareness and preserving the nation's cultural heritage.